The importance of cultural heritage: Reflections on muralism in the Universidad de Sonora - Olivas Castellanos, Elsa Catalina (UNIVERSIDAD DE SONORA, 2022)
Throughout history, muralism has been considered a key element in representing the identity of a cause, a movement and even a collective or a country. In Mexico, higher education (HE) institutions were also known for their various murals in their campuses through the last century. The case of the Universidad de Sonora (UNISON), one of the most important public HE institutions in the State of Sonora, is one that needs to be reevaluated in regards to the conservation, preservation and memory of its murals. In this paper we discuss why the murals of the UNISON must be preserved and recovered for the historical memory and their cultural legacy. The paper describes and reflects on the murals in the institution and how they are an integral part of the academic and historical experience. The conclusions point to a broader need to explore, rescue and promote such artistic expressions for generations to come.